Will Australia Raise the Minimum Age of Criminal Responsibility? - Crofts, Thomas (2019)
For many decades there have been calls for an increase in the minimum age of criminal responsibility (MACR) in Australia and in other common law jurisdictions. Despite this the State and Territory governments have largely been resilient to making any change. Such reluctance may, however, be set to change in Australia with the Government of the Northern Territory endorsing ‘in principle’ an increase in the MACR in the Northern Territory. This article examines the likelihood of the MACR being raised in the Northern Territory and theimpact this may have on the rest of Australia. It also considers what such an increase would mean for the rebuttable presumption of doli incapax which currently applies from the age of 10 until a child’s 14th birthday. This article argues that a higher minimum age level of criminal responsibility than 12 would be preferable but that this is a good step that will put the Northern Territory in line with other common law countries which have already made this change. It will also increase pressure on other Australian States and Territories and other countries which follow the traditional common law approach to raise their MACR. Finally, it argues that if the MACR is raised only to 12 the presumption of doli incapax should be retained for those aged 12 and 13